None of this is true : a novel - Jewell, Lisa (New York : Atria Books, 2023)
A woman who finds herself the subject of her own popular true crime podcast.
Keywords: Podcasters -- Fiction; Dysfunctional families -- Fiction; Secrecy -- Fiction; True crime stories -- Fiction; Detective and mystery fiction; Thrillers (Fiction); Psychological fiction